2020
DOI: 10.1007/s00024-020-02449-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Evolution of Drought Characteristics Over Hungary Between 1961 and 2010

Abstract: Historically, Hungary has witnessed numerous waves of drought episodes, causing significant agro-economic loss. Over the recent decades, the intensity, severity and frequency of drought occurrence have dramatically shifted, with undisputable upward tendencies across many areas. Thus, the main aim of this study was to characterize drought trends, intensity and duration over Hungary during 1961-2010. To attain the study goals, the present analyses utilized climate datasets obtained from Climate of the Carpathian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 62 publications
2
44
0
Order By: Relevance
“…Both the correlation coefficients and TE indicate a significant link during summer between the TPPI and Wolf number and between the TPPI and the geomagnetic index (for filtered data). The latter connection is slightly higher than the connection with the Wolf number at lag 2, which is highlighted by both methods and represents is an important result because European countries located in the Carpathian region are affected by drought episodes and present greater vulnerability to climate change 74 .…”
Section: Resultsmentioning
confidence: 74%
“…Both the correlation coefficients and TE indicate a significant link during summer between the TPPI and Wolf number and between the TPPI and the geomagnetic index (for filtered data). The latter connection is slightly higher than the connection with the Wolf number at lag 2, which is highlighted by both methods and represents is an important result because European countries located in the Carpathian region are affected by drought episodes and present greater vulnerability to climate change 74 .…”
Section: Resultsmentioning
confidence: 74%
“…The CARBATCLIM platform provides researchers with necessary climate data between 1960 and 2010 for the whole Carpathian Region (44 • N and 50 • N, 17 • E and 27 • E). This project was supported by the European Commission, and the output is a climate atlas with spatial resolution 0.1 • × 0.1 • [51,52]. Within the CARBATCLIM database, Hungary is covered by 1045 grid points (Figure 1), where each point contains all climate variables.…”
Section: Data Collection and Trend Analysismentioning
confidence: 99%
“…Similarly, Szép et al (2005) reported that soil conditions became drier during the twentieth Szinell et al (1998) detected an existing general drying tendency in Hungary. Alsafadi et al (2020) reported a significant increase (P < 0.05) of the area affected by very extreme drought in Hungary between 1960-2010. Bartholy et al (2013) predicted significant drought in Hungary for the period 2071-2100, due to the significant decrease of rainfall in the summer compared to 1961-1990 as a reference period Even though many studies had been conducted lately to analyze drought in Hungary, few studies deal with drought on the sub-regional scale.…”
Section: Introductionmentioning
confidence: 97%